(untitled) (Global Journal of Human-Social Science, 2019)
Acquiring jewelry education to become a jeweler in Ghana is either by School-Based or Apprenticeship. A concern expressed by some jewelry industry practitioners is that most students who acquire jewelry education through School-Based in Ghana are unable to practice as jewelers because there is a mismatch between skills that students acquired while in school and the jewelry industry’s needs. Correspondingly, Jewelry Apprenticeship has also saw a decline in patronage in recent times due to lack of regulatory framework, which has led to some Master and Apprentice Jewelers exploiting the training process. This study sought to conduct a comparative analysis to establish the similarities and differences that exist between these two Jewelry programmes. The study adopted the Mix Methods research approach with descriptive and evaluation as the research methods used. The researchers used Purposive and Snowball sampling techniques to draw a sample size of 300. Data collection tools used were observation, interview, and questionnaire.